Teammate influences on the eating attitudes and behaviours of athletes: A systematic review. (July 2019) - Scott, Charlotte L.; Haycraft, Emma; Plateau, Carolyn R.
Abstract: Background: It has been well documented that athletes are at an increased risk of developing disordered eating attitudes and behaviours. Over the last two decades, researchers have focused their attention on how teammates may influence athletes' eating attitudes and behaviours. Objective: To systematically review the literature relating to teammate influences on athletes' eating attitudes and behaviours. Method: A systematic literature search of the SPORTDiscus, PsycINFO and MEDLINE databases was conducted. Qualitative and quantitative studies were included if they met the following inclusion criteria: (1) examined the relationship between teammate influence and eating attitudes and/or behaviours; (2) sampled actively training athletes; (3) written in English; and (4) published in a peer-reviewed academic journal. Results: Twenty-four studies were included ( n  = 13 quantitative, n  = 11 qualitative). Included studies were found to be of good or reasonable quality. Mechanisms of influence were categorised as (1) Teammate support (e.g., supportive teammate friendships, promotion of healthy eating practices, vigilance against disordered eating), and (2) Teammate pressure (e.g., conflicting teammate friendships, critical comments and appearance conversations, maladaptive team norms, and competitive comparisons). Conclusion: Teammates are an important source of influence on athlete eating attitudes and behaviours and these influences can be protective against, or engender an increased risk for, disordered eating. Additional, prospective research is required to enhance understanding of the mechanisms of teammate influences and to inform the development of interventions to reduce disordered eating among athletes. Highlights: A systematic review of teammate influences on athlete eating practices was conducted. Teammates were vigilant against disordered eating and endorsed healthy eating practices. Critical comments and body comparisons among teammates promoted disordered eating. Psychoeducation interventions may help to address disordered eating among sport teams. Longitudinal research is needed to establish the temporal precedence of influences.